Perancangan dan Pembuatan Game Edukasi Pembelajaran Aritmatika untuk Siswa Kelas 1-3 SD - Rendy Suryadharma; Gregorius Satia Budhi; Kristo Radion Purba (Jurnal Infra, 2015)
Nowadays, educational games has been used as a medium of learning. Arithmetic is a branch of mathematics that studies the calculation of basic numbers, which are often used in various fields of life. Therefore, educational game for math learning can be used to assist students in learning arithmetic. The game is created using Adobe Flash Professional CS6 software and use the programming language Action Script 3.0. In the making of this game, the authors tested a similar educational game, in which the author will fix the shortcomings inherent in the educational game is a game that will be created. Therefore, the authors made a mathematical educational game that has a great view and interesting, so it can be liked by children.In this game, there will be five levels, which consists of gardens, lakes, parks, running track, and the train station. Any material given problem are distinguished based on the selected class, where the material contained on the grade 1 includes addition and subtraction, while in grade 2 and 3 includes a material addition, subtraction, multiplication, and division.Based on the results of the questionnaire, can be deduced that the game has been created it can be used as a medium of learning arithmetic for students, and to improve the capabilities and skills of students in the calculation of basic arithmetic operations.